Resonance frequency as a function of the time needed by epoxic glue to fix a probe - M, J.; Flores-Rosas, A.; Antonio-Torres, D.; A, J.; es-Avendaño.; Mendoza-Vazquez, S. (Revista Mexicana de Física, 2014)
In Atomic Force Microscope based in Quartz Tuning Fork, it is usual to attach, by epoxic glue, a probe to one of the prongs of the Quartz Tuning Fork and employ it as force sensor. This paper shows that the resonance frequency changes as a function of the required time by the epoxic glue to dry. Results of the resonance frequency shift measured at different moments of the experiment are also reported. It has been found that it is necessary to wait at least 10 hours to obtain a stable mechanical system. The results conclude that the studied phenomenon becomes important in the frequency-modulation AFM, due to the evolution of the resonance frequency along the entire experiment.